PREVALENCE AND MANAGEMENT OF OVARIAN TUMOURS IN WOMEN AND C HILDREN HOSPITAL ABBOTTABAD - ALAM, IQBAL; WAQAR, FAREESA; KHAN, ALAM; BEGUM, NAZAKAT (Journal of Ayub Medical College Abbottabad, 2001)
Background: I he purposes of study was to compare world incidence of ovarian tumours whether benign or malignant with that of '˜our unit. We have also discussed management of all these patients at our center. Results: In our unit out of total 1400 admissions in 24 months. 26 had ovarian tumours, out of these 6 were malignant. The overall malignancy in our unit was 23% as compared to 15% of overall world incidence 24 of these patients, were admitted through the OPD with advanced size of tumours. None of them previously had any checkup at proper Gynecological Centers. AH these 24 were admitted to the ward, investigated, operated and after receiving histopathology reports were further managed accordingly. Two patients had torsion of ovarian tumour and were admitted through emergency and operated as emergency cases in our study group the majority. 77% had benign ovarian tumours in which simple salpingoophorectomies was performed.